Traveling with Companions: The Social Customer Journey - Hamilton, Ryan; Ferraro, Rosellina; Haws, Kelly L.; Mukhopadhyay, Anirban (Journal of Marketing, 2021)
When customers journey from a need to a purchase decision and beyond, they rarely do so alone. This article introduces the social customer journey, which extends prior perspectives on the path to purchase by explicitly integrating the important role that social others play throughout the journey. The authors highlight the importance of “traveling companions,” who interact with the decision maker through one or more phases of the journey, and they argue that the social distance between the companion(s) and the decision maker is an important factor in how social influence affects that journey. They also consider customer journeys made by decision-making units consisting of multiple individuals and increasingly including artificial intelligence agents that can serve as surrogates for social others. The social customer journey concept integrates prior findings on social influences and customer journeys and highlights opportunities for new research within and across the various stages. Finally, the authors discuss several actionable marketing implications relevant to organizations’ engagement in the social customer journey, including managing influencers, shaping social interactions, and deploying technologies.